Interface Effect in Ir-Nb-Zr Alloy - Jian-Gang Yao; Yong Jiang; Ming-Chun Zhao; Deng-Feng Yin (Crystals)
The mechanical properties of Ir-Nb alloy have been significantly enhanced by the addition of solute Zr, yet there has been no quantitative explanation for this improvement. To address this issue, we investigated it from the perspective of Zr segregation to the Ir/Ir3Nb interface. The atomic-scale microstructures of three interfaces, namely Ir (100)/Ir3Nb(100), Ir(110)/Ir3Nb(110), and Ir(111)/Ir3Nb(111), were elucidated, along with the precise calculation of their interface energies using an unconventional method. This compensates for the deficiencies of the inaccurate results in calculating the interface energies of earlier prediction. Solute Zr prefers to segregate to the Ir/Ir3Nb interface by occupying Nb sites on the Ir matrix side, thereby improving the interface adhesion to some extent. High strength of interface region contributes to enhance the mechanical properties of Ir-Nb alloy, which is in agreement with the experimental observation as reported.